Optimizing Academic: The Impact of Kalyāṇamitta (Good Friends) on Learning Discipline - Sutiyono; Sutawan, Komang; Lestari, Widya (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
Research using a quantitative approach and aims to explore the influence of Kalyāṇamitta (Good Friends) on the discipline of young learning. This research focuses on the important role of good friends in shaping an individual's understanding of the discipline of learning. Data collected from 73 respondents using relevant instruments. Regression analysis is used to examine the relationship between an independent variable, namely Kalyāṇamitta (good friend), and a dependent variable. The statistical test results show that the regression model has a good quality, with a determination coefficient (R Square) of 0.234 (23.4%), and there are indications of other factors that influence self-improvement of 76.6%. The results of the analysis of regression cofficients show that Kalyāṇamitta practice has a significant and positive influence on the discipline of young learning. The implication is that Kalyāṇamitta (good friend) can be a factor that supports the development of understanding and practice of Buddhist teachings in the context of discipline learning.